Handbook of differential equations. - Canada, A.; Drabek, Pavel, 1953-; Fonda, Alessandro (Elsevier/North Holland, 2004)
This handbook is the second volume in a series devoted to self contained and up-to-date surveys in the theory of ordinary differential equations, written by leading researchers in the area. All contributors have made an additional effort to achieve readability for mathematicians and scientists from other related fields, in order to make the chapters of the volume accessible to a wide audience. . Six chapters covering a variety of problems in ordinary differential equations. . Both, pure mathematical research and real word applications are reflected . Written by leading researchers in the area.